Determinants of the subscription to bundled services and their effect on customer retention in the Korean communications sector - Moon-Koo Kim; Myeong-Cheol Park; Duk Hee Lee; Jong-Hyun Park (International Telecommunications Society (ITS), 2017)
Since bundlesprovide price discountsto customers and have lock-in effects forbusinessesin the communicationssector, the number of bundlesubscribersisrapidly growing in many countries,including Korea.The consumerwelfareand marketing effects of bundleshavebeen welldocumented. Existing literature, however,has paid little attention to identifyingthe facets of benefitsand risks that influence subscriptions, the differences in switching costs between subscribers and non-subscribers, and the relationships among bundle satisfaction, customerretention, and switching costs. To address these gaps, we performed an empirical analysis using survey data from 550 individuals.Our findingsshow that concernabout lock-inand performanceas well as economicbenefits influencesubscriptionsto the bundles, switching costs arehigher for thesubscribersthan for stand-alone service users, and monetary switching costsof bundlesdirectly affect customer retention. These results show the lock-in effectsofswitching costsof bundlesin subscribers' decision-making, retention, and churn. The implications for regulatory policyand customer strategyare discussed.
Keywords: 330; Service bundles; Bundling; Lock-in effects; Switching costs; Customer retention; Loyalty